Deep subsurface carbon cycling in the Nankai Trough (Japan)—Evidence of tectonically induced stimulation of a deep microbial biosphere. (26th September 2015) - Riedinger, N.; Strasser, M.; Harris, R. N.; Klockgether, G.; Lyons, T. W.; Screaton, E. J.
Abstract The abundance of microbial life and the sources of energy necessary for deep subsurface microbial communities remain enigmatic. Here we investigate deep microbial processes and their potential relationships to tectonic events in sediments from the Nankai Trough offshore Japan, drilled and sampled during IODP (Integrated Ocean Drilling Program) Expedition 316. Observed methane isotope profiles indicate that microbially mediated methane production occurs at Sites C0006 and C0007 in sediments below ∼450 meters below seafloor (mbsf) and ∼425 mbsf, respectively. The active carbon cycling in these deep subsurface sediments is likely related to the highly dynamic tectonic regime at Nankai Trough. We propose that transient increases in temperature have restimulated organic matter degradation at these distinct depths and explore several candidate processes for transient heating. Our favored hypothesis is frictional heating associated with earthquakes. In concert with transient heating leading to the reactivation of recalcitrant organic matter, the heterogeneous sedimentary system provides niches for microbial life. The newly available/accessible organic carbon compounds fuel the microbial community—resulting in an onset of methanogenesis several hundred meters below the seafloor. This process is captured in the methane C‐isotope signal, showing the efficacy of methane C‐isotopes for delineating locations of active microbial processes in deeply buried sediments. Additionally, simple model approaches applied to observed chemical pore water profiles can potentially constrain timing relationships, which can then be linked to causative tectonic events. Our results suggest the occurrence of slip‐to‐the‐trench earthquake(s) 200–400 year ago, which could relate to historical earthquakes (1707 Hoei and/or 1605 Keicho earthquakes).